The F2-layer parameter variations during spring equinox 2013, according to the Kharkiv and EISCAT incoherent scatter radars data - Zhivolup, T. G. (НТУ "ХПІ", 2014)
The investigations of temporal variations of the electron density in the F2-layer maximum, ion and electron temperatures in the mid-and high latitudes during the 2013 year spring equinox are conducted. The features of the temporal variations of the parameters of the F2-layer in Kharkiv and Tromsø during the spring equinox are revealed. It was established that during the spring equinox changes amplitude electron and ion temperatures in the ionosphere over Tromsø less than the amplitude of temperature changes of electrons and ions in the ionosphere over Kharkiv on the entire time interval of joint observations from 07:00 to 24:00 UT.

Проведено дослідження часових варіацій електронної концентрації в максимумі шару F2, іонної та електронної температур в середніх і високих широтах в період весняного рівнодення 2013 р. Виявлено особливості часових варіацій параметрів шару F2 в Харкові і Тромсьо в період весняного рівнодення. Встановлено, що в період весняного рівнодення амплітуди зміни температур електронів і іонів в іоносфері над Тромсьо менше, ніж амплітуди зміни температур електронів і іонів в іоносфері над Харковом на всьому часовому інтервалі спільних спостережень з 07:00 до 24:00 UT.
Keywords: spring equinox; temporal variations of the parameters; F2-layer; ionosphere; весняне рівнодення; часові варіації; шар F2